Morphological and Histological Characteristics of Testis of the Goby Glossogobius sparsipapillus Living from Coastal Estuaries from Bac Lieu to Ca Mau - Ton, Nguyen Huu Duc; Hien, Nguyen Thi Thuy; Canh, Tran Chi; Thao, Dang Hoa; Y, Nguyen Thi Nha; Quang, Dinh Minh (VNU Journal of Science: Natural Sciences and Technology, 2019)
This study was conducted in the coastal estuaries in Bac Lieu and Ca Mau provinces in order to provide data on morphological and histological characteristics of as well as the spermatocyte development at every stage of the development of testis of goby Glossogobius sparsipapillus . The analysis results of 226 fish individuals, collected monthly from April 2019 to September 2019 by using the bottom nets, showed that the testis of this fish was double strands. In stage I, testis was small, thin and transparent; and the weight and size of testis increased from that stage onward. The colour of the testis became ivory white with the smooth and puffed surface. Spermatogonia were found through the cross-section of the testis in stage I, and then they were divided into primary spermatocytes and secondary spermatocytes, which were interlaced in stage II. In stage III, spermatids appeared in testicular lobes and developed into sperm in stage IV. This fish species is a multiple spawner during the breeding season, because there are several developmental stages of spermatocytes in their histology. This result is the basis for further research on artificial reproduction of this fish. Keywords: Bac Lieu, Ca Mau, Glossogobius sparsipapillus , reproductive form, testis.Keywords: Essential oil plats, life form, plants, Sop Cop nature reserve. References [1] P. Akihito, K. Meguro, Glossogobius sparsipapillus, a new species of goby from Viet Nam. Japanese Journal of Ichthyology 23 (1976) 9-11. [2] D.D. Tran, K. Shibukawa, T.P. Nguyen, P.H. Ha, X.L. Tran, V.H. Mai & K. Utsugi, Fishes of Mekong Delta, Vietnam. Can Tho University Publisher, Can Tho, 2013 (In Vietnamese). [3] H.V. Nguyen, Freshwater fish of Viet Nam, Vol III, Agriculture Publishing House, Ha Noi, 2005 (In Vietnamese). [4] T.N. Nguyen, Fauna of Vietnam – Gobioidei, Science and Technics House Publishing, Ha Noi, 2000 (in Vietnamese). [5] H.M.T. To, T.M.X. Pham, V.H. Mai, D.D. Tran. Species composition of goby (Eleotridae and Gobiidae) and some characteristics of tank goby (G. giuris) distributed in Can Tho. Proceeding of Aqua Youth, Ho Chi Minh City (2013) 575-582 (in Vietnamese). [6] X.M.T. Pham, D.D. Tran, Some characteristics on reproductive biology of Tank goby (Glossogobus giuris) distributed in Can Tho city, Can Tho University Journal of Science 27 (2013) 161-168 (in Vietnamese). [7] Q.M. Dinh, T.V. Ly. Preliminary study result of length – weight of tank goby, Glossogobius giuris, distributing in Soc Trang, Can Tho University Journal of Science 2 (2014) 220-225. (in Vietnamese). [8] G.V. Nikolsky, Ecology of fishes, Academic Press, London, United Kingdom, 1963. [9] H.M. Carleton, R.A.B. Drury, E. Wallington, Carleton's Histological Technique, Oxford University Press, London, United Kingdom, 1980. [10] Q.M. Dinh, J.G. Qin, S. Dittmann, D.D. Tran, Reproductive biology of the burrow dwelling goby Parapocryptes serperaster. Ichthyological Research 63 (2016) 324–32. https://doi.org/ 10.1007/s10228-015-0502-7 [11] L. Bui, M.H. Nguyen, Q.K. Nguyen, Q.L. Le, D.Y. Mai, Basis of physiology of fish. Agriculture Publishing House, Ha Noi, 1985 (in Vietnamese). [12] P.J. Miller, The topology of gobioid fishes, G.W. Potts, R.J. Wootton (eds), The topology of gobioid fishes, Academic Press, Orlando, London, United Kingdom, 1984, 119-53 [13] Q.M. Dinh, T.T.G. Nguyen, T.K.T. Nguyen, Reproductive biology of the mudskipper Boleophthalmus boddarti in Soc Trang. Tap chi Sinh hoc 37 (2015) 362-9. https://doi.org/10. 15625/0866-7160/v37n3.6720 [14] Q.M. Dinh, T.T.M. Le, Reproductive traits of the duckbill sleeper Butis butis (Hamilton, 1822). Zoological Science 34 (2017) 452-8. https://doi. org/10.2108/zs170013. [15] N.H.T. Le, Q.M. Dinh, Reproductive pattern, morphological and histological characteristics of gonads of the goby Eleotris melanosoma from the Coastline in Soc Trang, VNU Journal of Science: Natural Sciences and Technology, 33 (2017) 9-86. http://doi.org/10.25073/2588-1140/ vnunst.4490 (in Vietnamese). [16] Q.M. Dinh, T.T.N. Tran, Reproductive biological traits of the goby Stigmatogobius pleurostigma (Bleeker, 1849) from the Mekong Delta, Vietnam. Indian Journal of Fisheries 65 (2018) 20-5. http://doi.org/10.21077/ijf.2018.65.1.681 88-04. [17] Q.M. Dinh, L.T. Tran, N.C. Ngo, T.B. Pham, T.T.K. Nguyen, Reproductive biology of the unique mudskipper Periophthalmodon septemradiatus living from estuary to upstream of the Hau River. Acta Zoologica(2018) 1-12. http://doi.org/10.1111/azo.12286.